The Relationship Between Religiosity, Media Literacy, And Psychological Resilience of Gen Z - Dewi, Danar Kristiana; Bintarti, Arifah (LPPM Universitas PGRI Sumatera Barat, 2025)
Generation Z lives in a digital environment that presents psychological challenges due to information overload, misinformation, and social media pressure. This study aims to examine the relationship between religiosity and media literacy with the psychological resilience of Generation Z in the digital era. This research applied a quantitative associative approach through questionnaires distributed to 100 Generation Z respondents in Central Java. The data were analyzed using SPSS with validity tests, reliability, correlation, and multiple linear regression. The findings reveal that religiosity and media literacy have a positive and significant effect on psychological resilience, with an R Square value of 0.679. This means that 67.9% of the variation in psychological resilience can be explained by these two independent variables. In conclusion, religiosity and media literacy are crucial factors in strengthening the psychological resilience of Generation Z in the digital era.